AL-AD’IYYAH AL-MA’TSŪRAH AND ITS USE in ARABIC LANGUAGE PRACTICE - Masoud, mahadi; Jalil, Marsufah Binti; Shamsudin, Jamsuri Bin Mohd (Universitas Ahmad Dahlan, 2018)
Some of challenging features faced by the Arabic language learners are lack of linguistic vocabulary, psychological motivation, the scarcity of cognitive and social materials, and the difficulty of practicing second or foreign languages among learners. Therefore, it is necessary to establish a search for elements and sources that help the leaners to face those difficulties. The researchers believe that the daily remembrance (dzikr) of the Qur’anic verses, the prophetic traditions, and the invocations (du’a) that Muslims deal with in their daily lives can be among the specific sources of Arabic language practice among non-Arab learners. Therefore, the researchers by using analytical and experimental approach chose some Arabic words or vocabulary from the popular invocations used by Muslims in their daily recitations and then presented it in the Arabic language classes. The researchers conducted three experiments on three groups of Malaysian junior students in Arabic subject in the second and third stages. The study found there are many sources that prevent the practice of the Arabic language. These barriers related to several factors such as the lack of language adaptation, psychological and behavioral conditions. However, the study concluded that good selection of vocabulary, or language phrases, especially from daily Islamic terms, drives Malaysian learners to practice Arabic.